The Influence of Competency and Organizational Culture on Employee Performance at the South Sulawesi Provincial Education Service - Andi Mappatompo; Rajib UI Sandi; Samsul Rizal (Pustaka Digital Indonesia, 2026)
This study is important because employee performance determines the success of government organizations. Declining performance due to low competence and a weakening organizational culture needs to be examined to provide an empirical basis for improving human resource management and the quality of public services. The objectives of this study are: 1) To determine the effect of competence on the performance of employees at the Education Department of South Sulawesi Province. 2) To determine the effect of organizational culture on the performance of employees at the Education Department of South Sulawesi Province. This study uses a quantitative method with an associative approach. The sample consists of the entire population, namely all employees of the Education Department of South Sulawesi Province, totaling 114 individuals. The results of this study indicate that competence has a positive and significant effect on employee performance. Therefore, efforts to enhance competence through training and professional development are crucial to improving employee performance at the Education Department of South Sulawesi Province. Organizational culture also has a positive and significant effect on employee performance. Hence, improving organizational culture through instilling positive values, enhancing communication, and developing a conducive work environment is essential to boost employee performance at the Education Department of South Sulawesi Province.